Clinical and Cerebral Metabolic Changes in Parkinson's Disease With Basal Forebrain Atrophy. Issue 5 (23rd January 2020) - Gang, Miyeong; Baba, Toru; Hosokai, Yoshiyuki; Nishio, Yoshiyuki; Kikuchi, Akio; Hirayama, Kazumi; Hasegawa, Takafumi; Aoki, Masashi; Takeda, Atsushi; Mori, Etsuro; Suzuki, Kyoko
Abstract: Background: Cholinergic dysfunction plays a key role in cognitive dysfunction in Parkinson's disease (PD). Recent studies revealed that atrophy in the nucleus basalis of Meynert (NBM), the largest cholinergic nucleus in the basal forebrain, heralds cognitive decline in PD. Despite clinical importance of NBM atrophy in PD, clinical and radiological correlates of NBM atrophy remains to be elucidated. Objective: We investigated the longitudinal changes in clinical and cerebral glucose metabolic characteristics in PD with atrophy in the NBM. Methods: We analyzed the 3‐year longitudinal data of 56 PD patients who underwent motor, nonmotor, and imaging evaluations at baseline. The patients were classified into PD with and without NBM atrophy based on the results of magnetic resonance imaging volumetry. We compared clinical characteristics and cerebral glucose metabolic changes between PD with and without NBM atrophy. Results: At baseline, 20 patients and 36 patients were classified into PD with and without NBM atrophy groups, respectively. At follow‐up, the data of the 14 PD patients in the NBM atrophy group and the 18 patients in the group without NBM atrophy completed full assessments and were available for the analysis. The PD with NBM atrophy group showed severe cognitive dysfunction and psychiatric symptoms both at baseline and follow‐up. The NBM volume significantly correlated with motor and nonmotor functions. The PD with NBM atrophy showed significantly reduced metabolism in the parietal and occipital cortices both at baseline and follow‐up. Conclusions: Basal forebrain atrophy is a simple and sensible marker of faster disease progression and cortical hypometabolism in PD. © 2020 International Parkinson and Movement Disorder Society